Investigation of Groundwater Recharges Mechanism in Alasehir Plain: From Physical Characterization To Modelling - Şimşek, Celalettin; Baba, Alper; Tayfur, Gökmen; Aksoy, Niyazi; Demirkıran, Zülfü; Hasözbek, Altuğ; Demirkesen, Ali Can; Tayfur, Gökmen; Baba, Alper; Kumanlıoğlu, Ahmet; Tonkul, Serhat; Durukan, Seda; et al. (International Water Association, 2017)
Characteristics of aquifer that allows the flow of groundwater, recharge and discharge mechanism effect the available groundwater potential. In order to determine the available potential of groundwater, the budget components are the most important parameters. In general, different analogical methods are applied in different countries, instead of using measurable data. Determination of the groundwater recharge is the most difficult parameter to be measured among the hydrological budget parameters. In general, the analogical methods are insufficient to determine the groundwater recharge rate. Precipitation, evaporation-transportation and runoff can be measured from the surface meteorological station. However, estimation of groundwater recharge cannot be measured directly. At the moment of climate change, visualization of the spatial distribution of the groundwater recharge estimation and mapping are needed. Therefore, improvements of easy groundwater recharge techniques are very important tools for groundwater basins to develop the water management planning.
IWA 2nd Regional Symposium on water, wastewater and environment, 22-24 March 2017, Cesme, İzmir
Keywords: Aquifer characterization; Recharge methods; Alaşehir